2000
DOI: 10.1046/j.1365-2524.2000.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Provider arrangements for mental health services in ‘The New NHS’

Abstract: Mental health services in England, in common with many other European countries, have been the subject of sustained government attention during the 1990s. Since the election of the Labour administration in Britain in May 1997, mental health services have been discussed in most Department of Health documents on health and social care policy, and mental health services in England have a new national strategy. At the same time, the local provision of mental health services within NHS Trusts has been undergoing or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…A key issue for CMHTs, therefore, is how they gate-keep access to their service [12]. Previous studies have suggested that gate-keeping decisions have been largely determined by individual clinicians and teams, rather than through formal strategic control [13]. Wells [14] described how the lack of prescriptive guidelines and under-resourcing at a local level, combined with a professional imperative to demonstrate the meeting of users' needs, was countered by the actions of individual practitioners reshaping users' perceptions of their needs to match available resources.…”
Section: Introductionmentioning
confidence: 99%
“…A key issue for CMHTs, therefore, is how they gate-keep access to their service [12]. Previous studies have suggested that gate-keeping decisions have been largely determined by individual clinicians and teams, rather than through formal strategic control [13]. Wells [14] described how the lack of prescriptive guidelines and under-resourcing at a local level, combined with a professional imperative to demonstrate the meeting of users' needs, was countered by the actions of individual practitioners reshaping users' perceptions of their needs to match available resources.…”
Section: Introductionmentioning
confidence: 99%
“…2001, Rosenheck et al . 2001); the need for evaluation of different service systems; and the use of goals to reach decisions about whether to use direct or indirect client treatment as a model for improving the service systems; (Badger et al . 2000, Barnes et al .…”
Section: Introductionmentioning
confidence: 99%
“…These views echo those of managers in company mergers. Peck and Hills (2000) monitored the emerging provider arrangements for the delivery of mental health services in the NHS during 1998 by reviewing documents relating to the proposed reconfiguration of 11 mental health services in England. They note that none cite any evidence in support of the benefits that are alleged to accrue from the proposed reconfiguration.…”
Section: Current Research On New Organizational Structures In Health mentioning
confidence: 99%